Analisis Konformitas Teman Sebaya dan Kesepian Dengan Perilaku Narsistik Siswa SMA Pengguna TikTok - Setiyowati, Arbin Janu; Erlita, Fania; Hotifah, Yuliati (Universitas Nusantara PGRI Kediri, 2023)
TikTok application users continue to increase every year, especially the various funny and interesting features in it. It is not surprising that TikTok has become one of the most popular social media in Indonesia, especially for teenage students. The purpose of this study, namely to determine the relationship between peer conformity and loneliness with the narcissistic behavior of high school students using TikTok. The research design uses quantitative methods with correlational types. The research population is 287 students who are actively using TikTok. The sampling technique used is simple random sampling with a total sample of 172 students. Collecting data using research instruments consisting of three attitude scales, namely the peer conformity scale, loneliness scale, and narcissistic behavior scale. Data analysis was performed using multiple linear regression analysis and Pearson's Product Moment. The results of this study indicate that there is a relationship between the three variables, namely peer conformity, loneliness, and narcissism.